Analisis Pola Aliran dan Kuantitas Air Tanah Dangkal di Kota Madiun - Nugraha, Setya; Alfahmi, Sirojudin; Hendro Cahyono, Hadi Wiwit (ENVIRO: Journal of Tropical Environmental Research, 2023)
The increasing physical development and decreasing water infiltration areas have led to a reduction in groundwater reserves. Groundwater is experiencing a decline both in quantity and quality over time. The rising demand for water is inversely proportional to the diminishing availability of water in terms of quality. This situation also implicates a decrease in the quantity of groundwater. Integrated protection and management efforts must be carried out from upstream to downstream, one of which can be achieved through groundwater conservation. Therefore, the aim of this research is to understand the shallow groundwater flow patterns in the city of Madiun. This study conducted an inventory, identification, and mapping of the area to determine the criticality of shallow groundwater in terms of quantity using the shallow groundwater flow pattern analysis method. The results of the analysis generally indicate that the direction of shallow groundwater flow in the city of Madiun, in the eastern areas of the Madiun River, flows from south to north, while in the western areas of the Madiun River, it flows from west to east, all ultimately leading towards the Madiun River.